Learning in Social Movements: A research study of awareness and understanding of a Treatment Literacy programme implemented by the Treatment Action Campaign in the Western Cape in the period 2001 to 2009 - Booysen, Fredalene (University of Cape Town, 2020)
This qualitative research study examines six participant's awareness and understanding of a Treatment Literacy (TL) programme implemented by the Treatment Action Campaign (TAC) in the Western Cape in the period 2001 to 2009. The study investigates what attracted the participants to the TAC; what they learnt and how this was taught; the extent, if any, to which participant's experiences changed their understanding of HIV and AIDS, sexuality, treatment and other health-related practices. To analyse participants' awareness levels, understanding and experiences, I drew on Freire (1970; 1985) and Mezirow (1991; 1994) adult education literature, more specifically literature addressing the social movements and how activists learn and teach in different context (informal and non-formal) such as Newman (1995) and Foley (1999). These perspectives underpin the central argument of the thesis, namely that adult education is contextual and has impact on awareness, understanding and experiences and in this case HIV and AIDS. A primary finding of the study is how the participants in the study perceived the world as central to their learning. Learning is thus a substantially personal experience; however, the development of the individual frequently occurs within a group dynamic. Participants felt that being part of TAC and fighting for access to treatment and helping other people who are either HIV positive or affected by HIV and AIDS, helped them in turn to deal with their own challenges of being HIV positive and affected with HIV and AIDS. Being HIV positive and receiving education from TAC has given participants dignity and the necessary consciousness to obtain control of their life. Participants also reported that the TL programme boosted their confidence and raised their level of awareness and understanding of the topic.